Elastix unified communications server cookbook : more than 140 real-life, hands-on recipes and tips to install, deploy, administer, and maintain any VoIP/Unified communications solution based on Elastix /: more than 140 real-life, hands-on recipes and tips to install, deploy, administer, and maintain any VoIP/Unified communications solution based on Elastix. (2015) - Barajas Puente, Gerardo
No abstract available